Peningkatan Ketrampilan Membaca Jarum Jam Menggunakan Alat Peraga Melalui Metode Demonstrasi Pada Siswa Kelas 1 SDN Ladong - Khairul Ismi (Departement of Mathematics Education, 2024)
As a leading implementation of education, a teacher is required to be able to design a method in the learning process that can make students become more interested, focused, enthusiastic in the learning process. On the subject of time material, there are still many students who have difficulty in mentioning the components of hours, minutes, seconds. The students' skills in reading the clockwork are still low. Here researchers conducted a classroom action study aimed at describing the improvement of clockwork reading skills in grade 1 students of SD Aisyiyah Unggul Gemolong. Researchers used a demonstration learning method that was carried out for two cycles. The subjects of this study were grade 1 students, totaling 33 students consisting of 17 male students and 16 female students. In each cycle there are several stages, namely planning, action, observation, and reflection. The results showed that there was an increase in learning outcomes with demonstration learning methods on clockwork reading material. Before any corrective action. The average score of students is 66.3 with a presentation completeness of 55%. In cycle 1, the average score of students increased to 68 with the presentation of completeness to 67%. While in cycle 2, the average student score became 76.3 and the presentation completeness was 82%. This shows that the use of demonstration learning methods can improve student learning outcomes of grade 1 reading material for grade 1 SDN Ladong